THE ROLE OF LAW IN INCREASING THE IMPLEMENTATION OF INFORMED CONSENT IN HOSPITALS BASED ON HEALTH LAW NUMBER 17 OF 2023 - Syifa Nadya Azzahra; Irsyam Risdawati; Marice Simarmata (RADJA PUBLIKA, 2025)
Informed consent is one of the fundamental aspects in medical practice, emphasizing the patient's right to give consent based on full understanding of the medical procedures they are about to undergo. The proper implementation of informed consent is crucial to safeguard the patient's rights and ensure that medical actions are performed ethically and professionally. The Health Law No. 17 of 2023 provides a clear legal foundation regarding the obligations of hospitals and medical personnel in carrying out informed consent. Article 56 of this Law states that